REAKSI PASAR DI SEPUTAR PENGUMUMAN PROPER (PROGRAM PENILAIAN PERINGKAT KINERJA PERUSAHAAN DALAM PENGELOLAAN LINGKUNGAN HIDUP ) - Verena Winardi Kusumo; Yeterina Widi Nugrahanti (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
The purpose of this research is to examine the change of market reaction around the date of Corporate Performanice Rating program in Environ mental management (PROPER) announcement and the change of market reaction between good PROPER rank and bad PROPER rank. The market reaction is measured by abnormal return and trading volume activity. The sample of the study consist of 25 companies which joined on PROPER and listed on the Indonesian Stock Exchange in 2009-2013. Data that used in this study consist of share’s daily closing price and daily trading volume. The research period is 7 days by using market-adjusted model. Analyzed technique for examining the hypothesis is Wilcoxon Signed Test at level significant of 5%. The result of this research shows that PROPER announcement get any response from the investor, because there were significant changes to the abnormal return. But there were no significant changes to the trading volume activity before and after PROPER announcement, abnormal return and trading volume activity between good PROPER rank and bad PROPER rank.